Genetic conservation of small populations of the endemic tree Swartzia glazioviana (Taub.) Glaz. (Leguminosae) in the Atlantic Forest - Spoladore, Janaína; Mansano, Vidal F.; Lemes, Maristerra R.; Freitas, Luan C.D. de; Magno Sebbenn, Alexandre (Conservation Genetics, 2017)
Swartzia glazioviana is a threatened legume tree species from the Brazilian Atlantic Forest characterized by aggregations of individuals and endemism to an area with extensive human occupation. It is critical to conduct studies on the species to conserve the remaining populations. Using ten nuclear microsatellite loci, we examined the genotypic and genetic diversity and structure, inbreeding, stand-level spatial genetic structure (SGS), effective population size, mating system, and pollen flow in three isolated remnant populations, aiming to inform conservation strategies. All adult individuals found in the populations were mapped and sampled and open-pollinated seeds were collected from two populations. The genotypic diversity (>0.85) indicates that sexual reproduction is predominant and the short distance between ramets indicates that asexual reproduction occurs by root development. In general, populations present SGS which is explained, in part, by root development. The genetic differentiation among populations was greater between more distant populations, suggesting a gene dispersal pattern of isolation by distance. Pollen flow (>27%) indicates that populations are not reproductively isolated, but fertilization followed an isolation by distance pattern. The outcrossing rate was high (tm > 0.8), but some mating occurred among related individuals (tm-ts > 0.1) and were correlated (rp > 0.15), indicating inbreeding and varying levels of relatedness within families. Inbreeding was higher in seed cohorts than adults, suggesting selection against inbred individuals between seed and adult stages. The results are discussed considering in situ conservation and strategies for seed collection for environmental reforestation. © 2017, Springer Science+Business Media Dordrecht.
Keywords: Conservation Genetics; Endangered Species; Endemic Species; Endemism; Gene Flow; Genetic Differentiation; Genetic Isolation; Genetic Marker; Genetic Structure; Legume; Relatedness; Seed Collection; Sexual Reproduction; Tropical Region; Atlantic Forest; Fabaceae; Swartzia